Consumer views on 'healthier' processed meat. Issue 7 (4th July 2016) - Shan, Liran Christine; Regan, Aine; Monahan, Frank J; Li, Chenguang; Murrin, Celine; Lalor, Fiona; Wall, Patrick G.; McConnon, Aine
Abstract : Purpose: The aim of this paper is to investigate consumer attitudes towards and interest in enriching processed meat with healthy ingredients ('functional meat'). Design/methodology/approach: Seven focus groups across age and gender were conducted. Discussions were analysed using an inductive thematic approach. Findings: Purpose - The aim of this paper is to investigate consumer attitudes towards and interest in enriching processed meat with healthy ingredients ('functional processed meat'). Design/methodology/approach - Seven focus groups stratified by age and gender were conducted. An inductive thematic analysis was carried out on the data. Findings - Strategies that participants felt as important for improving the healthiness of processed meat mainly included the use of better quality meat and less salt, fat, preservatives and other additives. 'Functional processed meat' was a new concept for participants. Four themes were constructed to reflect participants' attitudes towards functional processed meat: (i) Opposing views on processed meat as a carrier of healthy ingredients; (ii) Belief in the health benefits of functional processed meat; (iii) Perceived value of functional processed meat for different consumer groups; and (iv) Trust and perceived risk surrounding the functional food concept. A large proportion of the participants were unconvinced about the concept of functional processed meat; however many of the participants expressed an openness to purchase this food product if taste and price remained uncompromised. Research limitations/implications - Adopting a quantitative approach, the findings from this study should be explored further to investigate their application in a representative sample of the population. Originality/value - This study represents a first exploratory investigation of consumer views towards functional processed meat. It can inform further consumer and market research in relation to the development of 'healthier' processed meat. Research limitations/implications: The sample size of the current study is small. Complementary quantitative research with a more representative sample can be implemented. Originality/value: This study represents a first exploratory investigation of consumer views on functional meat. It can inform further consumer and market research in relation to the development of 'healthier' processed meat.